PERANCANGAN PEMESANAN MENU RESTORAN BERBASIS WEB UNTUK MENINGKATKAN SMART SERVICE MENGGUNAKAN METODE PRIORITY SCHEDULING - Niro, Armego; Ellbert Hutabri (Computer Science and Industrial Engineering, 2025)
Moon Cafe, located at Komplek Penuin Permai Blok B No. 2, faced challenges in menu management and ordering processes. With 94 printed menus, customers often waited their turn, and adding new menus required time and printing costs. The absence of a queue system increased errors, delays, and food waste due to unclear or incorrect orders. This study proposes a web-based ordering system using the Priority Scheduling method to prioritize orders based on cooking time and arrival order. The system, developed with Extreme Programming, ensures flexibility and responsiveness to operational needs. Results show improved efficiency in customer service, reduced recording and serving errors, and streamlined kitchen operations. The web-based system enables quick menu updates without additional costs, while prioritized order management minimizes delays and enhances customer satisfaction. This solution helps optimize Moon Cafe's operations and reduces material losses.